"Just Like the Other Boys": Meeting the Needs of Gender Diverse Students. (December 2016) - Croteau, Susan M.; Lewis, Katherine
Gary Armstrong, assistant principal, is faced with a delicate situation. The elementary school recently enrolled a transgender student, and the principal, Amy Lamar, is resistant to considering the student's unique needs. This case was developed for use in a leadership course. Instructors can use the case to encourage dialogue around legal frameworks, roles and perspectives of key characters, and theoretical perspectives informing decisions and policies. The four activities and discussion questions are designed to guide students in analyzing the scenario. The final activity involves comparing the scenario with a similar case with a different context and disparate outcomes.